Improving Sales Force Management towards Ensuring Adequate Training and Motivation of Sales People for Efficient and Effective Distribution of Unilever Products in Enugu - Okolo; O, Victor; John N, Uzor; Robert, Anuforo; Chinedum O, Obikeze; Gerald, Nebo; Jones N, Okafor (British Journal of Marketing Studies, 2015)
Improving sales force management towards ensuring adequate motivation and training of salespeople for efficient and effective distribution of Unilever products was studied. The sales force had had a hard time dealing with making higher sales without many extraneous and intervening variables. The specific objectives were to ascertain the degree of improving the relationship between sales force motivation and efficient and effective distribution of Unilever products and to determine the extent of improving the significant effect of training of sales force on efficient and effective distribution of Unilever products. The population of the study was 55 (45 sales representatives and 10 sales managers from 3 key distributors of Unilever Nigeria located in Enugu metropolis. The sample size is 48 using Taro Yamani sample size determination method. For the validity of the instrument, the questionnaire was vetted by research professionals based on face validity in terms of relevance to the subject matter, objective of the study, coverage of the content areas, appropriateness of language usage and clarity of purpose. The value of the test of reliability is 0.977 which was conducted using Cronbach’s Alpha. Primary data was adopted for the study. Pearson’s product moment correlation coefficient and simple linear regression data analyzing techniques was applied. The findings revealed that there is a significant degree of improvement in relationship between sales force motivation and efficient and effective distribution of Unilever products (r = 0.887, p < 0.05). And secondly, it was revealed that sales force training has an improved significant effect on efficient and effective distribution of Unilever products (r = 0.94; t = 18.585; F= 345.399; p < 0.05). The researcher is of the recommendation that firstly, that if the sales force is highly motivated, they will put in their best towards achieving greater success for the organization (Unilever). For the sales representatives, the laissez faire manner of operating gives them a sense of high esteem and belongingness to Unilever. Also, it is recommended that the sales force should undertake adequate training to make them more viable to efficiently and effectively distribute Unilever products. The general believe that salesmen are born is relegated here as adequate training is reiterated and resonated among sales managers.